Aspek Hukum Perlindungan Konsumen Produk Obat-Obatan Berdasarkan Bpom (Kasus Obat Sirop Tercemar Ed/Deg) - Zein, Syafira (UNES Law Review, 2023)
The Indonesian government is implementing regulations to improve public health services, focusing on providing, promoting, and implementing practical health care that is easy for the public to access and maintain. The first goal is to ensure that the public is treated as a consumer with all rights to receive treatment. However, technological advancements and economic development have led to increased demand for health services, particularly in the food sector. In recent years, there have been numerous cases involving children in various health care facilities. The Indonesian Food and Drug Authority (BPOM) has been tasked with ensuring that the food and nutrition services provided to the public are effective and safe. BPOM plays a crucial role in regulating the food and nutrition sector, providing necessary information and services to the public. The study aims to examine the role of BPOM in the food and nutrition sector, focusing on the legal aspects of consumer protection. The research uses a standardized research method to examine the legal norms and standards of food and nutrition products, focusing on the legal aspects of consumer protection. The study also examines the role of the government in implementing the food and nutrition sector in Indonesia. The findings will be used in a descriptive analysis to evaluate the effectiveness of the government's efforts in implementing the food and nutrition sector.